VITAMIN DEFICIENCY IN CHILDREN: MAIN CAUSES, FORMS, AND MEANS OF PREVENTION IN INFANTS AND PRESCHOOL CHILDREN - L.Yu. Volkova; M.A. Gurchenkova (Вопросы современной педиатрии, 2007)
The lecture deals with the main causes of development of hypo vitaminoses in infants and preschool children, with the emphasis made on the lack of pathognomonic signs of vitamin in sufficiency, showing the demands for the essential vitamins, and describing the natural sources of their entering the human body. The authors compare the composition of various multivitamin preparations registered in Russian the liquid dosage form convenient for use in 1ctoc7cyearcold children. Key words: avitaminosis, hypovitaminosis, prevention, infants, children.